PENGARUH NILAI BAKAR TERHADAP INTEGRITAS KELONGSONG ELEMEN BAKAR TRIGA 2000 - Alfa, Sudjatmi Kustituantini (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Bandung TRIGA reactor fuel element, which is a homogeneous mixture of uranium and zirconium hydride alloy shaped solid rod. At the time of reactor operation, the fuel temperature will increase with increasing high-power reactor, which will consequently increase the pressure of the gases that exist in the cladding. Pressures that arise in the fuel cladding is the sum of three components of the pressure, there are due to trapped air between the fuel cladding, fission gas pressure by forming and pressure stemming from the separation of hydrogen from zirconium hydride alloy. Fission gases generated by fuel depends on fuel burnup. The larger the value of a fuel burn, the greater the gaseous fission gases produced, consequently the greater the pressure inside the cladding caused by fission gas. The calculation of the amount of fission gases in the cladding which is a function of the fuel carried by using the program ORIGEN-2. ORIGEN-2 is a widely used computer code for calculating the build up, decay and processing of radioactive materials. The cross sections, fission product yields, decay data, decay photon data are either hard wired in the program or are made available as data libraries during the execution of the code. From the calculation results can be concluded that the gas pressure caused by fission gas is very small (4.13 10-3 psi) compared to the gas pressure caused by air trapped in the cladding that is equal to 56.6 psi, which resulted the cladding stres at 2080 psi. To ensure the integrity of fuel element cladding, the stress that occurs in the fuel cladding must be less than half the yield stress of cladding material, 12,000 psi at a temperature of 750 °C or about 40,000 psi at a temperature of 138 oC. It can be concluded that from the side of the fuel, then the fuel possible for use until the fuel burnup reaches a maximum value, in other words, the age of the fuel does not depend on the burnup of the fuel element.